2012
DOI: 10.1002/ajmg.b.32101
|View full text |Cite
|
Sign up to set email alerts
|

Association of KIBRA with episodic and working memory: A meta‐analysis

Abstract: WWC1 was first implicated in human cognition through a genome wide association study in 2006 that reported an association of the intronic single nucleotide polymorphism (SNP) rs17070145 with episodic memory performance. WWC1 encodes the protein KIBRA, which is almost ubiquitously expressed. Together with its binding partners, KIBRA is assumed to play a role in synaptic plasticity. T-allele carriers of SNP rs17070145 have been reported to outperform individuals that are homozygous for the C-allele in episodic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 61 publications
3
89
4
Order By: Relevance
“…As our studies continue to collect data, it will facilitate a more detailed examination of the influence of genetic variation in KIBRA and CLSTN2 on longitudinal memory performance and change in hippocampal volume. Also, even when we combined our cohorts to increase statistical power our sample size was relatively small, and a recent study indicated that in order to have 80 % power to detect an effect of KIBRA on episodic memory it requires a sample size of ~2000 individuals (Milnik et al, 2012). However, our subsample with hippocampal volume data was comparatively larger than most other studies previously reported (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As our studies continue to collect data, it will facilitate a more detailed examination of the influence of genetic variation in KIBRA and CLSTN2 on longitudinal memory performance and change in hippocampal volume. Also, even when we combined our cohorts to increase statistical power our sample size was relatively small, and a recent study indicated that in order to have 80 % power to detect an effect of KIBRA on episodic memory it requires a sample size of ~2000 individuals (Milnik et al, 2012). However, our subsample with hippocampal volume data was comparatively larger than most other studies previously reported (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the effect of the KIBRA SNP, rs17070145, on memory performance is still unclear, as indicated by a recent meta-analysis (Milnik et al, 2012) and review (Schwab et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, behavioral genetics studies have identified and characterized genetic variations associated with human memory performance [2,3]. These findings have been generated either by candidate-gene studies [4][5][6][7], which depend on pre-existing information, or by genome-wide association studies (GWAS), which allow to identify novel memory-related genes and molecular pathways [8,9]. However, memory performance is not a result of a single cognitive process, but rather the outcome of many, such as memory encoding, forgetting, or modulation of memory strength by emotional arousal.…”
Section: Introductionmentioning
confidence: 99%
“…Although many genetic variations associated with human memory performance have been identified (3)(4)(5)(6)(7)(8)(9), most were based on general memory scores, such as the number of recalled items. Such scores may serve as good correlates of overall memory ability, but they offer little insight into the genetic underpinnings of specific memory-related mental processes, such as encoding, memory maintenance, modulation by emotional arousal, or guessing strategies.…”
mentioning
confidence: 99%
“…GWAS already had identified a number of associations between single genetic markers and cognitive traits, such as episodic memory (7)(8)(9) and modulation of memory strength by negative emotional arousal (21). However, because many such traits are complex and multigenic, it is unlikely that a single genetic variant will explain a sufficient amount of behavioral variability.…”
mentioning
confidence: 99%